ENDOTHELIAL DYSFUNCTION – A KEY FACTOR IN ATHEROSCLEROSIS PATHOGENESIS - E. N. Vorobyeva; G. I. Shumakher; M. A. Khoreva; I. V. Osipova (Российский кардиологический журнал)
Endothelial dysfunction (ED) is currently considered as a key factor in atherosclerosis pathogenesis, and is manifested in disbalance between endothelial vasodilatators and vasoconstrictors. It has been demonstrated that virtually all atherogenic risk factors (RFs) act via ED. Therefore, ED parameters could be used as markers of early vascular atherosclerosis in people with atherogenic RFs. Early pathogenetic therapy in this group, as well as the treatment of the patients with confirmed atherosclerosis, could significantly improve prognosis.